Electroantennography in the study of two stingless bee species (Hymenoptera: meliponini) - E. F. L. R. A. Patricio; L. Cruz-López; E. D. Morgan (Brazilian Journal of Biology)
The first recorded electroantennographic preliminary studies on stingless bees have been performed using two species of Frieseomelitta from Brazil. Experiments with F. silvestrii and F. varia showed that antennae respond to hexane extracts of heads and abdomens of both species and posterior tibia of F. silvestrii (which carry plant resin), as well as to the pure compounds 2-heptanol and 2-nonanol, which occur in the mandibular glands of both species, and to the terpenes alpha-cubebene, humulene, and beta-caryophyllene found on their tibia and in the cerumen of their nests.